2021
DOI: 10.36941/ajis-2021-0105
|View full text |Cite
|
Sign up to set email alerts
|

The Intention of Investors in Making Investment Decisions in Sharia Stocks: Empirical Study in Indonesian

Abstract: This paper aims to examine the variables influencing the intention of Muslim investors in Indonesia in making sharia-stocks investment decisions. These variables are attitude, perceived behavioral control, religiosity, religious events, and profit maximization. Questionnaires are distributed to 150 respondents to collect data. This study selected respondents using the purposive sampling method. The criteria are (1) Active Muslim investors investing in sharia stocks (2) investors are not brokers or capital mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
12
0
4
Order By: Relevance
“…We assessed the investment intention by asking the participants whether they would invest their money to the entrepreneurial project (1= Strongly disagree; 5 = Strongly agree) from the scale developed by Septyanto, D., Sayidah, N., & Assagaf, A. [5]. Items included, "You invest in it out of faith", "You invest in it for further development", and "You invest in it for increasing wealth" (α = xxx).…”
Section: Methodsmentioning
confidence: 99%
“…We assessed the investment intention by asking the participants whether they would invest their money to the entrepreneurial project (1= Strongly disagree; 5 = Strongly agree) from the scale developed by Septyanto, D., Sayidah, N., & Assagaf, A. [5]. Items included, "You invest in it out of faith", "You invest in it for further development", and "You invest in it for increasing wealth" (α = xxx).…”
Section: Methodsmentioning
confidence: 99%
“…They found that large organizations are more susceptible to corporate sentiment than small companies. The stock performance may be explained by Islamic investor attitudes, suggested by Septyanto et al (2021) and Di et al (2021). Investor gloom and cross-section returns have a considerable negative association, according to Baker and Wurgler (2006).…”
Section: Islamic Investor's Sentimentsmentioning
confidence: 99%
“…The influence of family or friends using Islamic bank products, or the role of family or friends in choosing Islamic bank products in the form of information and encouragement from family or friends, is referred to as social influence (Rangkuti & Sulistyawati, 2014). Religiosity is Obedience in worship, carrying out worship activities diligently, attempting to have a broad knowledge of Islamic teachings, possessing a level of belief or a strong belief in carrying out Islamic teachings, carrying out all orders, and avoiding God's prohibitions (Audretsch et al, 2013;Bakar et al, 2013;Mahdzan et al, 2017;Moghavvemi & Musa, 2018;Muslichah & Sanusi, 2019;Septyanto et al, 2022). Salesperson service is the ability of product knowledge, selling skills, customer orientation, and experience (Oktavia, 2019;Saeed et al, 2013).…”
Section: Variable Measurementmentioning
confidence: 99%
“…Religiosity is defined as Islamic law-based behavior, such as always telling the truth, doing good, and not harming others (Dalrymple et al, 2012), having an Islamic personality, behaving sympathetically or kind to everyone, and being transparent and communicative (Aprianto & Candraningrum, 2020). The nature of religiosity is demonstrated by obeying God's commands while disregarding His prohibitions, being obedient to religion, working or engaging in various work activities with the goal of worship, and thinking optimistically and responsibly (Audretsch et al, 2013;Bakar et al, 2013;Mahdzan et al, 2017;Moghavvemi & Musa, 2018;Muslichah & Sanusi, 2019;Septyanto et al, 2022). Religiosity is a person's level of belief, trust, and piety in carrying out religious law.…”
Section: Introductionmentioning
confidence: 99%